2020
DOI: 10.1002/sce.21561
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of coherence in science teachers’ sensemaking of science‐specific formative assessment in professional development

Abstract: This study explores the role of conceptual coherence in science teacher learning of science‐specific formative assessment. Conceptual coherence refers to the alignment of ideas about teaching and learning and may be difficult with certain teaching practices, like formative assessment, that have a central role in accountability mechanisms in schools. The case study analyzes how one department of science teachers surfaced and managed issues of coherence as they developed and implemented science‐specific formativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
(69 reference statements)
2
22
0
Order By: Relevance
“…There are several implications for professional learning experiences for science teachers and for research arising from this study. If, as we argue, goal conflict is prevalent both when change is imposed upon teachers and when teachers themselves choose to make a change, then teacher educators may want to consider including opportunities for science teachers to examine and respond to potential goal conflicts in productive ways as part of educative experiences for science teachers (Heredia, 2020;Manz & Suarez, 2018). While we provided a week of professional development surrounding engineering and revising ADE and the SDCs, we did not provide structure for the teachers to revise their existing curriculum and pacing guides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several implications for professional learning experiences for science teachers and for research arising from this study. If, as we argue, goal conflict is prevalent both when change is imposed upon teachers and when teachers themselves choose to make a change, then teacher educators may want to consider including opportunities for science teachers to examine and respond to potential goal conflicts in productive ways as part of educative experiences for science teachers (Heredia, 2020;Manz & Suarez, 2018). While we provided a week of professional development surrounding engineering and revising ADE and the SDCs, we did not provide structure for the teachers to revise their existing curriculum and pacing guides.…”
Section: Discussionmentioning
confidence: 99%
“…One common thread among many studies on science teachers' conflicting goals is conflict appears to result from ambiguity in teachers' understanding of other's goals or expectations (Allen & Heredia, 2021;Allen & Penuel, 2015;Heredia, 2020;Johnson, 2013;Kelley & Finnigan, 2003;Smith & Southerland, 2007). Ambiguity often, but not always, coincides within a changing organizational context, such as the adoption of new standards (Allen & Heredia, 2021;Heredia, 2020). As one example, Heredia (2020) conducted a 3-year case study of seven science teachers enrolled in an ongoing professional development program while the district undertook curriculum HUTNER ET AL.…”
Section: Contextual Influences On Science Teachers Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet when faculty perceived some alignment between institutional policies, resources, and instructional change, such as an instructional improvement grant, they felt the resonance of institutional support and SLP participation bolstered their learning. A sensemaking lens allows for moving beyond a conceptualization of the tenure and promotion process as simply a barrier, and towards a more nuanced understanding of the ways dissonance and alignment stymie or support instructional innovation (Allen & Penuel, 2015; Heredia, 2020). Our findings indicate that incentives embedded in university structures (e.g., instructional innovation support grants) may create pivotal opportunities for alignment between faculties' personal quest for instructional change, external opportunities for pedagogical learning, and institutional policies.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the nature and strength of such norms and the social networks in which they are embedded, faculty may be averse to taking pedagogical risks (Kezar, 2014). In addition, how instructors adapt and implement instructional practices is often influenced by the alignment between new instructional practices and existing institutional structures and policies (Heredia, 2020). For example, in a study of teacher science PD, Allen and Penuel (2015) found teachers had difficulty incorporating the ideas of PD due to conflicting organizational goals regarding curriculum and instruction.…”
Section: Theoretical Frameworkmentioning
confidence: 99%